Volume 2: Biomedical and Biotechnology Engineering 2010
DOI: 10.1115/imece2010-38245
|View full text |Cite
|
Sign up to set email alerts
|

Pump Design for a Portable Renal Replacement System

Abstract: This work proposes a small, light, valve-less pump design for a portable renal replacement system. By analyzing the working principle of the pump and exploring the design space using an analytical pump model, we developed a novel design for a cam-driven finger pump. Several cams sequentially compress fingers, which compress flexible tubes, thus eliminating valves. Either changing the speed of the motor or size of the tube can control the flow rate. In vitro experiments conducted with whole blood using the pump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The advantage of this design is that alternating pressure waves across the capillary dialyzer reduces protein deposition on the membrane surface, so improving transfer of larger solutes and middle molecules [7]. Alternative designs to develop smaller more ergonomically efficient blood pumps for dialysis include ripple pump technology, in which a series of fingers are aligned on both sides of the blood tubing, and controlled by a cam mounted on a shaft and oriented at different angles so that they sequentially activate the fingers to propel blood forward [8].…”
Section: Improving the Design Of The Extracorporeal Circuitmentioning
confidence: 99%
“…The advantage of this design is that alternating pressure waves across the capillary dialyzer reduces protein deposition on the membrane surface, so improving transfer of larger solutes and middle molecules [7]. Alternative designs to develop smaller more ergonomically efficient blood pumps for dialysis include ripple pump technology, in which a series of fingers are aligned on both sides of the blood tubing, and controlled by a cam mounted on a shaft and oriented at different angles so that they sequentially activate the fingers to propel blood forward [8].…”
Section: Improving the Design Of The Extracorporeal Circuitmentioning
confidence: 99%
“…To address the demand for portable home haemodialysis devices, initial investigations demonstrated that substantial improvements in pump size and eciency were possible [191,192]. An alternative to the roller pump, called a nger pump, has been developed by…”
Section: Summary and Previewmentioning
confidence: 99%
“…Kang [192]. The nger pump maintains the benets of traditional positive displacement roller pumps (i.e., no uid contamination) with the added benets of higher eciency and smaller size compared to pumps with a similar ow rate, as well as a reduction in clotting when pumping biological uids.…”
Section: Summary and Previewmentioning
confidence: 99%
See 2 more Smart Citations